Implementation of the Richmond Agitation-Sedation Scale (palliative version) on an inpatient palliative care unit - Bush, Shirley H.; Bronicki, Katarzyna; Dionne, Michel; Lelievre, Natasha; Lawlor, Peter G.; Kabir, Monisha (Université d'Ottawa | University of Ottawa, 2023)
Abstract Background The Richmond Agitation-Sedation Scale – Palliative version (RASS-PAL) tool is a brief observational tool to quantify a patient’s level of agitation or sedation. The objective of this study was to implement the RASS-PAL tool on an inpatient palliative care unit and evaluate the implementation process. Methods Quality improvement implementation project using a short online RASS-PAL self-learning module and point-of-care tool. Participants were staff working on a 31-bed inpatient palliative care unit who completed the RASS-PAL self-learning module and online evaluation survey. Results The self-learning module was completed by 49/50 (98%) of regular palliative care unit staff (nurses, physicians, allied health, and other palliative care unit staff). The completion rate of the self-learning module by both regular and casual palliative care unit staff was 63/77 (82%). The follow-up online evaluation survey was completed by 23/50 (46%) of respondents who regularly worked on the palliative care unit. Respondents agreed (14/26; 54%) or strongly agreed (10/26; 38%) that the self-learning module was implemented successfully, with 100% agreement that it was effective for their educational needs. Conclusion Using an online self-learning module is an effective method to engage and educate interprofessional staff on the RASS-PAL tool as part of an implementation strategy.